2021
DOI: 10.3390/app11209695
|View full text |Cite
|
Sign up to set email alerts
|

Robust Static Structural System Identification Using Rotations

Abstract: Deflections are commonly measured in the static structural system identification of structures. Comparatively less attention has been paid to the possibility of measuring rotations for structural system identification purposes, despite the many advantages of using inclinometers, such as a high resolution and being reference free. Although some work using rotations can be found in the literature, this paper, for the very first time, proposes a statistical analysis that justifies the theoretical advantage of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Among the wide array of monitoring devices, inclinometers, commonly referred to as tilt sensors, deserve special attention for their widespread application across SHM [35]. For instance, in the context of bridge health assessment, researchers such as Huseynov et al [36] employed rotation measurements from inclinometers to detect structural damage, while in building structural analysis, Jun et al [37] demonstrated the efficiency of inclinometer-derived rotation data to efficiently identify damage in building beams.…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide array of monitoring devices, inclinometers, commonly referred to as tilt sensors, deserve special attention for their widespread application across SHM [35]. For instance, in the context of bridge health assessment, researchers such as Huseynov et al [36] employed rotation measurements from inclinometers to detect structural damage, while in building structural analysis, Jun et al [37] demonstrated the efficiency of inclinometer-derived rotation data to efficiently identify damage in building beams.…”
Section: Introductionmentioning
confidence: 99%